Peningkatan Soft Skill Siswa SMA Melalui Critical Lesson Study Pada Mata Pelajaran IPS Terpadu - Siti Alifah (Peneliti.net, 2019)
Educators must realize that students are unique creatures that have distinctive differences, such as differences in intelligence, interests, talents, hobbies, behavior and attitudes. In addition, their differences are also caused in terms of social, economic, and family care background. For this reason, educators must understand the differences in individual students in order to be able to serve education in accordance with these differences. The existence of teacher knowledge about students' differences will deliver the development and potential of students optimally. That is, educators who provide learning according to the development and needs of students in accordance with the development of students are inseparable from soft skills and and the methods used in Learning. Sample is taken from high school students in the city of Bekasi, as many as 30 students. One of the approaches used is the critical lesso study. Improvement is expected to be realized. This research method uses 2 cycles of classroom action research methods. The results of my research, the critical LSson study approach can improve students' soft skills, as much as 0.6.